Analysis of Rahn and Murabahah Financing in Baitul Maal Wa Tamwil (BMT): Qualitative Study of Agricultural Businesses in Kanigoro, Blitar Regency, Indonesia - Yusuf, Saifudin; Imam Nur Ngaini; Ulin Nuha (Open Access Indonesia Journal of Social Sciences, 2024)
The agricultural sector in Indonesia plays an important role in supporting food security and economic stability. However, this sector is still faced with various obstacles, one of which is limited access to capital. Baitul Maal Wa Tamwil (BMT) as an Islamic microfinance institution offers financing solutions for farmers using sharia principles, such as rahn and murabahah. This research aims to analyze the rahn and murabahah financing schemes implemented by BMT in Kanigoro, Blitar Regency, as well as their impact on agricultural businesses in the area. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with BMT administrators, rahn and murabahah financing customers, as well as other related parties. The data analysis technique was carried out using thematic analysis. BMT in Kanigoro, Blitar Regency implements rahn and murabahah financing schemes with sharia principles in accordance with the provisions of the Islamic religion. Rahn financing uses collateral, while murabahah financing uses a buying and selling system with an agreed profit margin. BMT rahn and murabahah financing has several advantages compared to conventional financing, namely: Based on sharia principles that avoid usury; Easy and fast application process; Competitive interest rates; Assistance and coaching for customers. However, BMT also faces several challenges in carrying out this financing, namely: Lack of public understanding about sharia financing; Strict requirements for applying for financing; High risk of crop failure. In conclusion, the rahn and murabahah financing offered by BMT in Kanigoro, Blitar Regency is an alternative solution for farmers in accessing capital. The implementation of this financing scheme has a positive impact on agricultural businesses and improves farmer welfare.